Influence of Environment Conditions on Ultrasonic and Electrostatic Precipitation of Aerosols of Wood Flour - Maria Yur'evna STEPKINA; Olga Borisovna KUDRYASHOVA; Alexandra Alexandrovna ANTONNIKOVA (Archives of Acoustics, 2020)
The risk of human exposure to finely-dispersed aerosol particles being airborne indoors is determined by the size and the number concentration of particles, the intensity of an aerosol emission source, the air filtration and ventilation efficiency, etc. The emphasis in this article is on behaviour patterns of aerosol particles when exposed to ultrasonic and electrostatic fields in different conditions of air temperature and relative humidity. Wood flour having sizes of interest (characteristic particle diameter about 10 μm) is chosen as a model aerosol. The article considers a physical and mathematical model presenting the evolution of aerosol particles in external fields, taking into account the moisture content and the temperature of a dispersive medium. The efficiency of ultrasonic and electrostatic precipitation in different relative humidity and temperature conditions in an enclosed space was studied using optical measurement methods of particle size and concentration.